Comparison of two methods of dental age estimation in 7-15-year-old Malays - Mani, S.A.; Naing, L.; John, J.; Samsudin, A.R. (2008)
Background. Numerous methods of age estimation have been proposed. The Demirjian method is the most frequently used, which was first applied in a French Canadian population in 1973. The Willems method is a modification of the above and was applied in a Belgian population in 2002. Objectives. The objectives of this study were to test the applicability of the two methods, namely Demirjian and Willems, for age estimation in a Malay population, and to find the correlation between body mass index and the difference between the dental age and the chronological age. Materials and Methods. A cross-sectional study involving 214 boys and 214 girls, selected by a simple stratified random sampling method was carried out. The orthopantomograph was used to score the seven left mandibular teeth, and the calculated maturity score was used to obtain the Demirjian dental age. Willems dental age was estimated using the tables proposed in the Willems method. Results. The Demirjian method overestimated the age by 0.75 and 0.61 years, while the Willems method overestimated the age by 0.55 and 0.41 years among boys and girls, respectively. In boys, the body mass index was significantly correlated to the difference in age using the Willems method. Conclusion. Further modification of either method is indicated for dental age estimation among the Malay population.